From the Mahalla to the Mikrorajon: Urbanization and Identity Construction in Soviet Central Asia (KULT_online, 2011)
The one-dimensional view on Stalinism as a mere history of violence has to be complemented by new approaches that emphasize the perspective of the civilization mission the Soviet regime envisioned for the geographical edge of the USSR. Beside the study of urbanization and industrialization processes, the achievements of the education system and of the cultural-linguistic russification of the indigenous people thereby becomes much more important, too. Looking at the Uzbek metropolis, the historian Paul Stronski for the first time investigates all these phenomena with regard to the whole of Central Asia, namely for the period in which the sleepy town of Tashkent entered into the modern age, and which formed the city's profile to a decisive extent, even more so than the collapse of the Soviet Union. As his study points out, this social and economic change isn't described sufficiently by terms like 'coercion' and 'terror' alone. The everyday life of the citizens was instead influenced by typical symptoms of deficiency that accompanied the Soviet regime constantly.